Pancasila as Juridical Basis in the Merdeka Curriculum in Primary Schools - Pambudi, Gigih; Yudha, Vidia Pandji; Hidayat, Sholeh (Universitas PGRI Sumatera Barat, 2023)
Education in elementary schools has a central role in forming students' character and independence. The Merdeka Curriculum as an innovation in the field of education in Indonesia emphasizes student independence and the development of their potential. However, its implementation requires a deep understanding of the legal aspects of education. The juridical basis is key in ensuring the conformity of the Merdeka Curriculum with the applicable legal framework. The aim of this study is to explores the role of juridical foundations in implementing the Merdeka curriculum in elementary schools. This research was designed using qualitative methods using a library research approach (literature review). The research results show that the Pancasila educational philosophy has to become the main foundation in the national education system. Pancasila recognizes the truth of knowledge that comes from revelation, reason and experience. As a regulatory norm that must be upheld, Pancasila is a guideline in the legal order in Indonesia. A deep understanding of Pancasila values is very important in realizing education that reflects its basic principles. It is hoped that the consistent application of the Pancasila educational philosophy can encourage the realization of Indonesian human development in accordance with the values reflected in Pancasila as the state philosophy and ideology.